Líquenes y hongos liquenícolas epífitos de Quercus ilex L., poco conocidos en encinares de Cataluña (España) (Cryptogamie Mycologie, 1999)
We present here 13 species of lichens and 3 of lichenicolous fungi found on Quercus ilex L. in evergreen oak forests of Catalonia. Leptogium coralloideum (Meyen & Flotow) Vainio, Scoliciosporum gallurae Vězda & Poelt, Abrothallus microspermus Tul. are new reports for Spain, and nine more species are new for the flora of Catalonia. For each one of them, a brief morphological characterisation, its distribution in Europe and in the Iberian Peninsula, and its autoecology are given.